(untitled) (Third Sector Social Economic Review, 2017)
Entrepreneurship is important for the economic development of an country. Entrepreneurship; it is the process of perceiving an opportunity to set up or grow a new business from a profit-oriented business and to create a new product or service. (Yılmaz and Sünbül, 2009). Cooperatives can be defined as a combination of solidarity and economic forces to make sure that the people who trust each other to achieve a certain goal can not do the work alone or the more useful things to do together at a cost price (Uzel, 1970, Mülayim, 2013). In order to increase women’s labor force, to promote women’s social and cultural activities and to increase women’s employment, in the direction of the demands of female entrepreneurs, our country published the example article of the Ministry of Customs and Trade under the name of ""Woman Entrepreneur Production and Operation Cooperative"" in 2013 and many new women cooperatives were established (Başaran , et al., 2015). When the structure of cooperatives, one of the most important building blocks for the economy in this country, is examined, it is seen that the number of women cooperatives is low. The reason for the selection of Baci Yanı Meram, who constitutes the case of our work, is the lack of a similar cooperative structure in Turkey. Increasing the number of such cooperatives is important to increase the number of women entrepreneurs.